ANALISIS TINGKAT KESELAMATAN PENGGUNA JALAN DI PERLINTASAN SEBIDANG PT KERETA API INDONESIA (STUDI KASUS DI DAOP 1 KOTA JAKARTA) - Fudjia Orva Nurani (2022)
Accidents at the crossing of a plot often occur every year, especially in the Operational Area 1 of Jakarta City. Factors that cause accidents such as systems and technical safety devices and other safety support facilities. However, there is one important factor that also plays a role in the occurrence of accidents at the crossing of a plot, namely the behavioral factor of road users. Therefore, this study aims to get an overview of the behavior of road users at the crossing of a plot that can increase the risk of accidents. The method in this study uses a qualitative approach through field observations and interviews. The field observation method is aimed at studying violations as well as analyzing aspects of the applied safety system. The officer interview method is aimed at obtaining the chronology of the accident as well as obtaining a characteristic picture of the crossing of the plot studied. The method of interviewing road users is aimed at obtaining data that describes the behavior and decision-making carried out by road users at the crossing of a plot. Based on the results of the study, it was found that the number of violations committed by road users is quite high. In addition, the characteristics of the crossing of a plot indicated by the condition of the road contours, the safety system, the volume of road users, as well as the duration of waiting and the duration of passage of road users do not comply with the rules. The conclusions of this study show that the behavior of road users that threatens safety is influenced by predisposing factors, supporting factors, and driving factors. Such behavior can be minimized by implementing risk mitigation measures through the implementation of avoidance and reduction strategies. For avoidance strategies, stakeholders can use preventive and repressive approaches. The reducing strategy can be carried out with the HFACS approach on the safety system aspect as well as the BBS approach on the road user behavior aspect. In the HFACS approach, an internal evaluation of the implementation of the safety system by stakeholders is carried out. Meanwhile, the BBS approach is evaluated based on the behavior of road users towards safety at the crossing of a plot